(untitled) (Colombia Medica, 2016)
Objective:To analyze if there is an association between the presence of polymorphisms in the LPL gene (rs320, rs285 and rs328) with development of acute ischemic stroke in Colombian population. Methods:In a case control design, 133 acute ischemic stroke patients (clinical diagnosis and x-ray CT) and 269 subjects without stroke as controls were studied. PCR -RFLP technique was used to detect rs320, rs285 and rs328 polymorphisms in the LPL gene. Results:In the present research was not found any association between any of the LPL gene polymorphism and acute ischemic stroke in the population studied; the allele and genotypic frequencies of the studied polymorphisms were similar in cases and controls and followed the Hardy-Weinberg equilibrium. The study was approved by the IRB and each subject signed the informed consent. Conclusion:LPL gene polymorphisms are not genetic markers for the development of stroke in the Colombian sample used.